THE SIGNIFICANCE OF THE WORKS OF MAHMUDKHOJ BEHBUDI TODAY (International Conference on Modern Science and Scientific Studies, 2025)
This article talks about the significance of the activities of Mahmudhodji Behbudi in a short period of time and recognizes his influence on current socio-economic, political and religious processes. Also, in his journalistic articles it is revealed that he raised current and pressing problems of the development of the Motherland, society, people and nation, often influenced by the spirit of independence.